Physics, asked by anjali12302, 2 months ago

When a polynomial f(x) is divided by x-3 and x+6 , the respective remainders are 7 and 22. What is the remainder when f(x) is divided by (x-3)(x+6)​

Answers

Answered by Radhaisback2434
2

Explanation:

When ever a polynomial of degree N is divided by another polynomial of degree < N, the remainder will always be a polynomial ONE degree less than degree of denominator.

Remainder Theorem states that if a function f(x) is divided by (x-a), then f(a) is the remainder.

Taking cognizance of above two facts, we know the remainder when f(x) is divided by (x-3)(x+6) will be linear polynomial of degree ONE.

Let the remainder be represented by Ax + B

If f(x) is divided by x-3, remainder is 7

=> 3A + B = 7

If f(x) is divided by x-(-6), remainder is 22

=> -6A + B = 22

Solving the two equations, we get A = -15/9 & B = 12

So final remainder is -15x/9 + 12

Hope its help..

Answered by LaRouge
81

Answer:

f(x) = (x – 3)(some polynomial) + 7 so that f(3) = 7

f(x) = (x + 6)(some other polynomial) + 22 so that f( – 6 ) = 22

when f(x) is divided by a quadratic factor the remainder is of the form ax + b

f(x) = (x – 3)(x + 6)(yet another polynomial) + ax + b

subs x = 3: 7 = 3a + b

subs x = – 6: 22 = – 6a + b

subtracting these we get – 15 = 9a

hope help uh❣️❣️❣️❣️

Similar questions